Spectroscopic properties of polycarbonate and poly(methyl methacrylate) blends doped with Europium(III) acetylacetonate - Bonzanini, R.; Dias, D. T.; Girotto, E. M.; Muniz, E. C.; Baesso, M. L.; Caiut, JMA; Messaddeq, Younes [UNESP]; Ribeiro, SJL; Bento, A. C.; Rubira, A. F. (Elsevier B.V., 2006)
Spectroscopic properties of blends formed by bisphenol-A polycarbonate (PC) and poly(methyl methacrylate) (PMMA) doped with Europium (III) acetylacetonate [Eu(acac)(3)], have been studied by photoacoustic spectroscopy (PAS) and photoluminescent (PL) spectroscopy. Emission and excitation spectra, excited state decay times, and quantum efficiency have been evaluated as well. PAS studies evidenced chemical interactions between the Europium complex and the PC/PMMA blend, which presented typical percolation threshold behavior regarding the Eu3+ content. PL spectra evidenced the photoluminescence of the Eu3+ incorporated into the blend. Photoluminescence property enhancement was observed for the composite in comparison with the precursor compound. Optimized emission quantum efficiency was observed for the 60/40 blend doped with 2% and 4% Europium (III) acetylacetonate. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: polymer; Eu3+-beta-diketonate complex; photoacoustic spectroscopy; photoluminescence